BUILD USING NETWORK LAN ROUTER CAN DO TO FULL CONTROL OF ACCESS SERVER - Sutarno st Sutarno (Majalah SIKOMTEK, 2010)
Local Area Network (LAN) is a network where companies hardware and software coupled to each other can communicate in a specific work area using the data and has a high speed, so that two or more networks can communicate with another network which is situated very far in order can perform a full access control from servers to workstations, workstation her as controlling management of a network by using routers.